1987
DOI: 10.1017/s0022112087002866
|View full text |Cite
|
Sign up to set email alerts
|

Secondary instability of a temporally growing mixing layer

Abstract: The three-dimensional stability of two-dimensional vortical states of planar mixing layers is studied by direct numerical integration of the Navier-Stokes equations. Small-scale instabilities are shown to exist for spanwise scales at which classical linear modes are stable. These modes grow on convective timescales, extract their energy from the mean flow and exist at moderately low Reynolds numbers. Their growth rates are comparable with the most rapidly growing inviscid instability and with the growth rates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

27
154
0
1

Year Published

1992
1992
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 324 publications
(182 citation statements)
references
References 23 publications
27
154
0
1
Order By: Relevance
“…The algorithm was parallelized and typically executed on 8 to 20 CPUs. As a test of the numerical model, the results of Metcalfe et al (1987) for the transition in a free shear layer with Re = 400 and N = 0 were reproduced with good agreement.…”
Section: Nonlinear Evolution and Transition To Turbulencementioning
confidence: 91%
See 3 more Smart Citations
“…The algorithm was parallelized and typically executed on 8 to 20 CPUs. As a test of the numerical model, the results of Metcalfe et al (1987) for the transition in a free shear layer with Re = 400 and N = 0 were reproduced with good agreement.…”
Section: Nonlinear Evolution and Transition To Turbulencementioning
confidence: 91%
“…We can assume that the mechanism leading to these waves is the elliptic instability of strained vortices (Kerswell 2002). Vortical structures similar to the 'ribs' in the 'braid' regions (Metcalfe et al 1987) were observed at some stages of the flow evolution. There are also substantial differences between the magnetic and non-magnetic cases because of the suppression and re-orientation of the secondary structures by the magnetic field and the fact that in the magnetic case the rolls are not perpendicular to the mean flow.…”
Section: Nonlinear Evolution and Transition To Turbulencementioning
confidence: 98%
See 2 more Smart Citations
“…[12][13][14] When moving from two to three dimensions, it is found that many hydrodynamic and MHD configurations may become unstable to the so called secondary instability. [15][16][17][18][19][20][21] The initial equilibrium starts off being unstable to a twodimensional ͑2D͒ instability ͑primary instability͒ that grows, driving the system to a new 2D configuration that is itself unstable to ideal three-dimensional ͑3D͒ modes that can drive the system toward a turbulent state. It has been shown that the 2D nonlinearly saturated configuration of an initial current sheet subjected to the tearing instability develops an ideal instability that has growth rates exceeding the reconnection rate.…”
Section: Introductionmentioning
confidence: 99%